The applicability of Awan Larat motif on modern typeface representing the Malay identity / Siti Sarah Adam Wan and Mohd Zaki Mohd Fadil - Adam Wan, Siti Sarah; Mohd Fadil, Mohd Zaki (Faculty of Art and Design, 2022)
The selection of typeface is more than merely picking aesthetically pleasing typefaces; it is a crucial aspect of any digital design. In Graphic Design to have aesthetic appeal, it must have a clear visual hierarchy, a well-balanced design, and an overall tone that is consistent throughout. Other media such as wood carving patterns, murals, and graffiti art may also incorporate such typefaces. The design idea shall govern the precise patterns and motifs that could be applied to the typeface to make it more visually pleasant to the eye. One of the popular traditional ornaments in wood carving worn in Malaysia, known as Awan Larat. However, this traditional ornament, becoming increasingly irrelevant in the contemporary world. This is occurring due to technological improvements and a general lack of interest and appreciation on the side of the new generation of Malay population. The aim of this research is to determine that the Awan Larat motif can be adopted on a modern font representing the Malay identity on typefaces. As a result, the researcher was able to demonstrate how well the element of the Malay identity could blend with a modern font. This font can be used for a variety of purposes, including book and magazine covers, advertising, logos, and signage, among others. By using appealing fonts as a source of inspiration for native Malay components, it is possible to indirectly contribute to the development of Malay identity both inside and outside of Malaysia. It is hoped that this research will provide a better understanding of the significance of using this traditional motif in a modern typeface to raise awareness of the Malay people's cultural heritage values.